2019
DOI: 10.1111/aji.13102
|View full text |Cite
|
Sign up to set email alerts
|

Are B cells altered in the decidua of women with preterm or term labor?

Abstract: Problem The immunophenotype of B cells at the maternal‐fetal interface (decidua) in labor at term and preterm labor is poorly understood. Method of study Decidual tissues were obtained from women with preterm or term labor and from non‐labor gestational age‐matched controls. Immunophenotyping of decidual B cells was performed using multicolor flow cytometry. Results (a) In the absence of acute or chronic chorioamnionitis, total B cells were more abundant in the decidua parietalis of women who delivered preterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 202 publications
(181 reference statements)
2
19
0
Order By: Relevance
“…These results are consistent with our results of a ∼1.5fold increase in CD19 + CD20 + B cells numbers in the decidua parietalis in Rhesus macaque exposed to intraamniotic LPS compared to IA saline controls (84). Functionally, B cells were reported to be protective for preterm birth in mice via IL-33 and progesterone-induced blocking factor, decreasing LPS induced neutrophil recruitment (139), although this protective action has been questioned in a recent study (138).…”
Section: B Cellssupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with our results of a ∼1.5fold increase in CD19 + CD20 + B cells numbers in the decidua parietalis in Rhesus macaque exposed to intraamniotic LPS compared to IA saline controls (84). Functionally, B cells were reported to be protective for preterm birth in mice via IL-33 and progesterone-induced blocking factor, decreasing LPS induced neutrophil recruitment (139), although this protective action has been questioned in a recent study (138).…”
Section: B Cellssupporting
confidence: 91%
“…Furthermore, B cell frequency did not significantly change during the course of pregnancy in decidua basalis even during systemic inflammation (231). However, the frequency of CD19 + B cells were higher in the decidua parietalis of women who underwent preterm birth regardless of labor (138,139). These results are consistent with our results of a ∼1.5fold increase in CD19 + CD20 + B cells numbers in the decidua parietalis in Rhesus macaque exposed to intraamniotic LPS compared to IA saline controls (84).…”
Section: B Cellssupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, IL‐35 was tested in the decidua of women after delivery. These studies showed for the first time that the frequency of B cells (CD45 + CD3 ‐ CD19 + CD20 + ) expressing IL‐35 was higher than the percentage of these cells expressing other cytokines (IFN‐γ, IL‐2, IL‐4, IL‐6, IL‐10, IL‐12, TNF‐α) in the decidua basalis …”
Section: Resultsmentioning
confidence: 93%
“…Our laboratory and others have extensively demonstrated that the B cell compartment undergoes significant adaptations during pregnancy, apparently to support the acceptance of the semiallogeneic fetus (12)(13)(14)(15)(16)(17)(18)(19) and to avoid the occurrence of immune mediated pregnancy disorders, like preterm birth (PTB) among others (15,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Moreover, it has recently been demonstrated that decidual B cells, through a mechanism involving IL-33, can control inflammation induced by bacterial components and significantly reduce the occurrence of PTB (31).…”
Section: Introductionmentioning
confidence: 99%